Improving maternal and infant health through acupressure - Lisda Widianti Longgupa; Nurmiaty Nurmiaty; Christina Entoh; Fransisca Noya; Sony Bernike Magdalena Sitorus; Kadar Ramadhan; Nurfatimah Nurfatimah; Putri Mulia Sakti; Febti Kuswanti; Khuzaifah Khuzaifah; Marlina Lailatul K (Universitas Muhammadiyah Magelang, 2024)
A prevalent experience among pregnant women is discomfort. Acupressure, a cornerstone of Traditional Chinese Medicine (TCM), seeks to harmonize the body's energy flow through meridian points postulated to be interconnected with internal organs. This community outreach initiative sought to augment the capabilities of pregnant women and caregivers of infants/toddlers in self-acupressure and neonatal/infant acupressure within Lantojaya Village, Poso Pesisir District, Poso Regency. The methodology encompassed lectures, interactive question-and-answer sessions, discussions, and practical demonstrations. The outcomes revealed a discernible shift in participants' knowledge concerning acupressure principles and their proficiency in applying acupressure to specific part of body.